coloniality and early childhood education: a critical analysis of pedagogical practices in an institution in a peripheral brazilian context - ferreira da silva, otavio henrique (childhood & philosophy, 2024)
This article aims to critically examine the presence of colonial influences within the pedagogical practices of an early childhood education institution situated in a culturally peripheral area of Brazil. Our examination is based on insights gathered from both educators and families involved in the institution. The argumentation and theoretical framework utilized draw from childhood studies as well as decolonial and counter-colonial theories. The data analyzed in the article stems from conversations held with adults who participated in the research. Specifically, four interviews were conducted with teachers and mothers of children attending the early childhood education institution in Betim – MG, a city characterized by its peripheral and predominantly black population. Through these interviews, the article sheds light on the grievances expressed by participants, which collectively delineate what the authors define as the coloniality of early childhood education. One significant aspect highlighted by both teachers and mothers is the discomfort generated during meal times, a routine occurrence within the pedagogical setting. This discomfort is attributed to acts of violence perpetrated against children during these moments. Such violence is construed as an embodiment of adultcentrism, a concept denoting the relegation of children to the periphery of the Western civilizational narrative. Adultcentrism is further characterized as a product of the Eurocentric and colonial paradigm, akin to a pervasive affliction affecting educational practices.The authors advocate for concerted efforts to combat coloniality and adultcentrism within early childhood education, emphasizing the necessity of grounding this endeavor in practical experiences rather than purely theoretical frameworks. They underscore the imperative of enhancing teacher training programs to foster awareness regarding the need for counter-colonial approaches within early childhood education. Ultimately, the article posits the pursuit of an emancipatory society as contingent upon the simultaneous advancement of counter-colonial initiatives within the realm of early childhood education.